Effectiveness of Rural Youth Tutoring Activity in Increasing ChildrenÔÇÖs Learning Motivation in Pandemic Era - Afria Ulin Nuha; Hidayatu Munawaroh (Universitas Islam negeri Mahmud Yunus Batusangkar, 2022)
COVID-19 pandemic has changed all aspects of peopleÔÇÖs lives in Indonesia, including the early childhood education. This study aims to determine the effectiveness of tutoring activities by young people in villages to improve childrenÔÇÖs learning motivation amid pandemic era. This was experimental method of quantitative research. Purposive sampling technique was used to choose the sample. The instrument to collect the data was observation checklist and the data were analyzed using Wilcoxon test. Results showed that during pandemic era, learning tutoring activities by the young people in rural area was effective in improving childrenÔÇÖs learning motivation. Thus, environment has a positive effect on motivating children to learn through appropriate games in tutoring activities.┬á┬á ┬á┬á